ANALISIS PRODUKSI PETANI PADI DI KECAMATAN ANJONGAN KABUPATEN PONTIANAK - B01108065, Alexander Passa (Jurnal Pembangunan dan Pemerataan, 2013)
This thesis is titled ''Analysis of Farmers Rice Production In Sub-district Anjongan district Pontianak''. The problem in this study is'' What Factors Affect The Production of Rice Farmers in District Anjongan Being Pontianak regency. While the purpose of this study was to determine the factors that influence the production of rice farmers in the district annually Anjongan Pontianak regency, analyzing production cost, revenue and profit / loss of peasant farms. In this study, the writer uses descriptive method that reveals conditions that occur in the field as it is based on the facts found during the field research. Data collection techniques used is to use a tool koesioner in the form of questions that come with alternative answers addressed to a sample of respondents in this study and data collection of the institutions or agencies in the District Anjongan Pontianak regency. Based on the results of research conducted in the field, it can be concluded that the amount of costs to be incurred by each farmer respondents was Rp 5,931,858 per hectare with an average total revenue obtained by the respondent farmers was Rp 23,564,718 per hectare with the level of benefits farmers respondents from land use 1 hectare was Rp 17,632,860 per hectare, while the level of farm productivity resulting in Pontianak regency Anjongan District from land use 1 hectare is equal to The role of government in this case the local agricultural agencies is needed by farmers, namely in terms of providing the kinds of new rice seed varieties that have passed the eligibility test for region growing agricultural area in District Anjongan. It is expected that the new rice varieties can be one choice of seeds for farmers in Sub Anjongan so that local farmers no longer depend on the choice of the type of quality seeds alone. Keyw0rd: Analysis of Farmers Rice Production In Sub Anjongan Pontianak regency